2013
DOI: 10.1523/jneurosci.5350-12.2013
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal Homosynaptic and Heterosynaptic Long-Term Plasticity of Corticogeniculate Projection Neurons in Layer VI of the Mouse Visual Cortex

Abstract: Most neurons in layer VI of the visual cortex project to the dorsal lateral geniculate nucleus (dLGN).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 53 publications
2
21
0
Order By: Relevance
“…The reason for the absence of significant change of group-averages might be the balanced nature of heterosynaptic plasticity. It is also important to note that in articles specifically aimed at investigating heterosynaptic plasticity, it was readily induced by regular pairing (Arami and others 2013; Huang and others 2008; Nishiyama and others 2000), afferent tetanization (Bauer and LeDoux 2004; Chevalyre and others 2003; Cummings and others 1996; Nugent and others 2007; Pascual and others 2005; Royer and Paré 2003; Staubli and Ji 1996; Wöhrl and others 2007), or purely postsynaptic protocols (e.g., Christofi and others 1993; Cummings and others 1996; Pockett and others 1990). This analysis substantiates our conclusion that induction of homosynaptic plasticity by a typical pairing procedure used in STDP studies is accompanied by induction of heterosynaptic plasticity in unpaired inputs.…”
Section: Induction Of Input-specific and Heterosynaptic Plasticity: Smentioning
confidence: 99%
See 1 more Smart Citation
“…The reason for the absence of significant change of group-averages might be the balanced nature of heterosynaptic plasticity. It is also important to note that in articles specifically aimed at investigating heterosynaptic plasticity, it was readily induced by regular pairing (Arami and others 2013; Huang and others 2008; Nishiyama and others 2000), afferent tetanization (Bauer and LeDoux 2004; Chevalyre and others 2003; Cummings and others 1996; Nugent and others 2007; Pascual and others 2005; Royer and Paré 2003; Staubli and Ji 1996; Wöhrl and others 2007), or purely postsynaptic protocols (e.g., Christofi and others 1993; Cummings and others 1996; Pockett and others 1990). This analysis substantiates our conclusion that induction of homosynaptic plasticity by a typical pairing procedure used in STDP studies is accompanied by induction of heterosynaptic plasticity in unpaired inputs.…”
Section: Induction Of Input-specific and Heterosynaptic Plasticity: Smentioning
confidence: 99%
“…Indeed, the rise of [Ca 2+ ] in is sufficient to induce plasticity (Neveu and Zucker 1996; Yang and others 1999). Induction of long-term heterosynaptic plasticity by intracellular tetanization and other protocols was impaired or blocked by chelation of intracellular calcium with EGTA (Arami and others 2013; Bright and Brickley 2008; Han and Heinemann 2013; Lee and others 2012; Nugent and others 2007). Substantial rise of [Ca 2+ ] in is produced by bursts of back-propagating action potentials activating voltage-dependent calcium channels (Miyakawa and others 1992; Petrozzino and Connor 1994; Schiller and others 1995; Schiller and others 1998; Yuste and Denk 1995), and can be further amplified by calcium release from internal stores (Berridge 1998; Fagni and others 2000; Nakamura and others 1999).…”
Section: Induction Of Input-specific and Heterosynaptic Plasticity: Smentioning
confidence: 99%
“…It has been shown to be concurrently present in the hippocampal dentate gyrus with the perforant afferents [10] [13], while as well in the hippocampal CA1 region [14]. Besides, it has further been reported that the concurrent homosynaptic LTP and heterosynaptic LTD also occur in visual cortex [15]. These are all important regions in brain for memory.…”
Section: Memory As Concurrent Homosynaptic Ltp and Heterosynaptic Ltdmentioning
confidence: 99%
“…LTD is induced by low-frequency protocol in the WM/L-VI to L-IV in younger animals when inhibitory postsynaptic potentials (IPSPs) are blocked (20). Previous studies show that LTD in visual cortex is induced mostly in synapses in layers II/III, IV, and V (17,18). In the authors previous study, in CG neurons of L-VI, it was found that cannabinoid type 1 receptors and calcineurin under-lie the UL-induced and WM-induced het-LTD, respectively.…”
Section: Ltd Of Epspsmentioning
confidence: 99%
“…In the authors previous study, in CG neurons of L-VI, it was found that cannabinoid type 1 receptors and calcineurin under-lie the UL-induced and WM-induced het-LTD, respectively. Therefore, homosynaptic LTP and heterosynaptic LTD in these cells may change the synaptic transmission efficacy by different underlying mechanisms (18).…”
Section: Ltd Of Epspsmentioning
confidence: 99%